SYSTEMATIC LITERATURE REVIEW: METAPHOR, PROTOTYPE, AND MEANING ANALYSIS IN COGNITIVE LINGUISTIC STUDIES - Mufidah Nur Amalia (Universitas PGRI Palembang, 2025)
This study aims to compile a systematic review of the use of metaphors, prototypes, and meaning analysis within the scope of cognitive linguistics through a Systematic Literature Review (SLR) approach. Cognitive linguistics is a branch of linguistics that examines the relationship between language, thought, and human experience. This field focuses on three key concepts: conceptual metaphor, prototype structure, and the dynamics of meaning analysis. This review involves analyzing relevant literature, including journal articles, books, and research reports, to identify patterns, trends, and gaps in previous studies. The findings indicate that conceptual metaphors play a crucial role in representing human experience, while prototype theory provides insights into conceptual categories and meaning perception. Furthermore, meaning analysis within cognitive linguistics tends to be interdisciplinary, involving cognitive psychology, anthropology, and computer science. This study also highlights that the integration of digital technology in cognitive linguistic analysis presents new opportunities for developing more accurate methods. Overall, this research provides a comprehensive mapping of current literature and offers recommendations for future research directions, particularly in applying cognitive linguistics to understand language and cultural phenomena.